Haemorrhagic Bowel Syndrome in Fattenig Pigs - Novotný Jaroslav (Sciendo, 2016)
The aim of this work was to determine the possible causes of sudden death in fattening pigs associated with haemorrhagic bowel syndrome (HBS) in a commercial pig farm (Eastern Slovakia). The etiology and pathogenesis of haemorrhagic bowel syndrome is not clearly defined within the scientific community. For this reason, clinical examination and sampling from 90 kg finisher pigs was done. Samples of blood, faeces, and rectal swabs were taken for haematological, serological, bacteriological, virological, and parasitological examination. Necropsy and sampling was also conducted on the carcasses of 90 kg finisher pigs that died peracutely during the investigation period. Three weeks later, during slaughter of the same group of pigs, goal-directed investigation and sampling from the gastrointestinal system for histological examination was performed. Results show the presence of bloody diarrhoea caused by L. intracellularis, C. perfringens typ A and haemolytic E. coli. Inflammation and loss of blood led to moderate normochromic (haemoglobin 12.85±0.95 g.dl-1) normocytic anaemia (erythrocytes 3.38±0.17 T.l-1), hydremia (haematocrit 0.17±0.01 l.l-1) and mild leukocytosis (18.7±4.68 G.l-1). Diagnostic necropsy confirmed the picture of “haemorrhagic bowel syndrome„ caused by infection and subsequent enterotoxemia without presence of gastric or intestinal displacement. Slaughter examination showed picture of proliferative ileitis typical for L. intracellularis. On the basis of our examinations, a major role in haemorrhagic bowel syndrome played infectious agents such as L. intracellularis, C. perfringens typ A and haemolytic E. coli. Negative findings of salmonellosis, dysentery, feed mycotoxins, intestinal parasites, and pollution of drinking water exclude these factors from the etiology of haemorrhagic bowel syndrome.